If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(2y + 3) + -1(2y + 3) = 7 Reorder the terms: 2x(3 + 2y) + -1(2y + 3) = 7 (3 * 2x + 2y * 2x) + -1(2y + 3) = 7 (6x + 4xy) + -1(2y + 3) = 7 Reorder the terms: 6x + 4xy + -1(3 + 2y) = 7 6x + 4xy + (3 * -1 + 2y * -1) = 7 6x + 4xy + (-3 + -2y) = 7 Reorder the terms: -3 + 6x + 4xy + -2y = 7 Solving -3 + 6x + 4xy + -2y = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 6x + 4xy + 3 + -2y = 7 + 3 Reorder the terms: -3 + 3 + 6x + 4xy + -2y = 7 + 3 Combine like terms: -3 + 3 = 0 0 + 6x + 4xy + -2y = 7 + 3 6x + 4xy + -2y = 7 + 3 Combine like terms: 7 + 3 = 10 6x + 4xy + -2y = 10 Add '2y' to each side of the equation. 6x + 4xy + -2y + 2y = 10 + 2y Combine like terms: -2y + 2y = 0 6x + 4xy + 0 = 10 + 2y 6x + 4xy = 10 + 2y Reorder the terms: -10 + 6x + 4xy + -2y = 10 + 2y + -10 + -2y Reorder the terms: -10 + 6x + 4xy + -2y = 10 + -10 + 2y + -2y Combine like terms: 10 + -10 = 0 -10 + 6x + 4xy + -2y = 0 + 2y + -2y -10 + 6x + 4xy + -2y = 2y + -2y Combine like terms: 2y + -2y = 0 -10 + 6x + 4xy + -2y = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-5 + 3x + 2xy + -1y) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-5 + 3x + 2xy + -1y)' equal to zero and attempt to solve: Simplifying -5 + 3x + 2xy + -1y = 0 Solving -5 + 3x + 2xy + -1y = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 3x + 2xy + 5 + -1y = 0 + 5 Reorder the terms: -5 + 5 + 3x + 2xy + -1y = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 3x + 2xy + -1y = 0 + 5 3x + 2xy + -1y = 0 + 5 Combine like terms: 0 + 5 = 5 3x + 2xy + -1y = 5 Add 'y' to each side of the equation. 3x + 2xy + -1y + y = 5 + y Combine like terms: -1y + y = 0 3x + 2xy + 0 = 5 + y 3x + 2xy = 5 + y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 0=-16x^2-16x+5 | | -9*-2-3y=6 | | 9-3f=60 | | 5h+2(h-11)=-5 | | 7x=8x+-4 | | y=-16x^2-16x+5 | | 3x+12x-7=5x+3 | | X+19x=180 | | -16t^2+40t+40=0 | | (fg)(x)=-16x^2-16x+5 | | .10n+.25(n+5)=5.10 | | 3y+15=6x | | 5e+8=53 | | sinx=0.1 | | 4x-1=(15+2x) | | 71=-6(2-8x)+5(8x-1) | | 8x-24=8x+3(8+2x) | | 7-2exp(x)=0 | | 8x-12=-2(-4x+4) | | 73=-7x-3(-4x-16) | | e=6p-1x-2 | | .10+.25(n+5)=4.40 | | logx=3.6 | | 73=-7x-39(-4x-16) | | 75-10-8+12-18=x | | 5x+1/8=0.5 | | 5(x-6)=7x-6 | | exp(x)-2=4 | | 17+8=-3c-25 | | 36=5(3c-12)+4(2c+1) | | exp(7x)=8 | | 75-10-8+12=x |